Constraint-induced movement therapy alleviates motor impairment by inhibiting the accumulation of neutrophil extracellular traps in ischemic cortex - Congqin Li; Jian Hu; Ying Xing; Jing Han; Anjing Zhang; Yuqian Zhang; Yan Hua; Zhanzhuang Tian; Yulong Bai (Neurobiology of Disease, 2023)
Stroke is a major cause of mortality and morbidity and most acute strokes are ischemic. Evidence-based medicine has demonstrated the effectiveness of constraint-induced movement therapy (CIMT) in the recovery of motor function in patients after ischemic stroke, but the specific treatment mechanism remains unclear. Herein, our integrated transcriptomics and multiple enrichment analysis studies, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and gene set enrichment analysis (GSEA) studies show that CIMT conduction broadly curtails immune response, neutrophil chemotaxis, and chemokine-mediated signaling pathway, CCR chemokine receptor binding. Those suggest the potential effect of CIMT on neutrophils in ischemic mice brain parenchyma. Recent studies have found that accumulating granulocytes release extracellular web-like structures composed of DNA and proteins called neutrophil extracellular traps (NETs), which destruct neurological function primarily by disrupting the blood–brain barrier and promoting thrombosis. However, the temporal and spatial distribution of neutrophils and their released NETs in parenchyma and their damaging effects on nerve cells remain unclear. Thus, utilizing immunofluorescence and flow cytometry, our analyses uncovered that NETs erode multiple regions such as primary motor cortex (M1), striatum (Str), nucleus of the vertical limb of the diagonal band (VDB), nucleus of the horizontal limb of the diagonal band (HDB) and medial septal nucleus (MS), and persist in the brain parenchyma for at least 14 days, while CIMT can reduce the content of NETs and chemokines CCL2 and CCL5 in M1. Intriguingly, CIMT failed to further reduce neurological deficits after inhibiting the NET formation by pharmacologic inhibition of peptidylarginine deiminase 4 (PAD4). Collectively, these results demonstrate that CIMT could alleviate cerebral ischemic injury induced locomotor deficits by modulating the activation of neutrophils. These data are expected to provide direct evidence for the expression of NETs in ischemic brain parenchyma and novel insights into the mechanisms of CIMT protecting against ischemic brain injury.